1979
DOI: 10.1021/bi00586a004
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium ion dependent adenosine triphosphatase activity of heavy meromyosin as a function of temperature between +20 and -15.degree.C

Abstract: The hydrolysis of Mg2+-adenosine 5'-triphosphate (ATP) by heavy meromyosin has been studied between +20 and -15 degrees C, especially in the low-temperature range, in a medium containing 30% (v/v) ethylene glycol by fluorometric, spectrophotometric, and potentiometric measurements. The time course of the fluorescence changes of the enzyme during the reaction depends markedly on the temperature in consequence of large differences between the activation energies of the various steps. The observed kinetics have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
29
0

Year Published

1979
1979
1987
1987

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 48 publications
5
29
0
Order By: Relevance
“…Further studies on the reaction pathway of myosin by rapid reaction techniques at low temperatures should clarify the effect of temperature on the equilibria of the various intermediates. Fluorescence studies at low temperature have lead to similar conclusions to our work [33].…”
Section: Spectroscopic Studies On Myosin S1 During Mg-a Tpase Catalysissupporting
confidence: 88%
“…Further studies on the reaction pathway of myosin by rapid reaction techniques at low temperatures should clarify the effect of temperature on the equilibria of the various intermediates. Fluorescence studies at low temperature have lead to similar conclusions to our work [33].…”
Section: Spectroscopic Studies On Myosin S1 During Mg-a Tpase Catalysissupporting
confidence: 88%
“…Heavy meromyosin and actin were prepared and characterized as described [12, 131. Actin was dialyzed before use against a 5 mM Tris/HCl buffer containing 6 mM KC1 and 3.6 mM MgC12; its reduced viscosity [q] was equal to 9.8 f 0.95 dl/g at 25 "C in this solution.…”
Section: Methodsmentioning
confidence: 99%
“…Purity of myosin was checked by polyacrylamide gel electrophoresis in the presence of sodium dodecyl sulphate; the patterns showed a very intense heavychain band and three light-chain bands in the expected staining ratios. Solutions of minifilaments were kept at 4°C and used between three days after their preparation.Heavy meromyosin and actin were prepared and characterized as described [12, 131. Actin was dialyzed before use against a 5 mM Tris/HCl buffer containing 6 mM KC1 and 3.6 mM MgC12; its reduced viscosity [q] was equal to 9.8 f 0.95 dl/g at 25 "C in this solution.…”
mentioning
confidence: 99%
“…The nucleotide-promoted specific cleavages (steps 3 and 4 in the digestion scheme) seem to reflect the changes in myosin heavy-chain conformation upon nucleotide binding that have been detected by a variety of other techniques [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][49][50][51]]. Here we show that the same conformational change is promoted by lowering the temperature.…”
Section: Discussionmentioning
confidence: 99%
“…That the binding of ATP is also a three-step process [49] has been shown unambigously by ATP-chase experiments [50] and by using 1,P-ethenoadenosinetriphosphate, a fluorescent analogue of ATP [51]. These and other studies have shown that the equilibrium constant for the transition between the two forms of binary nucleotide-myosin complexes varies with temperature, ionic strength and pH [28,29,32,33, 35-37, 52, 531. The results have been interpreted as indicating that the myosin head itself exists in two conformational states in equilibrium which depends on ambient factors and is perturbed by the binding of nucleotides [36, 37, 52, 541.…”
mentioning
confidence: 99%